Impact of mustard biodiesel and clove oil additives on particulate matter emission and carbon deposition in diesel engines - Bhangwar, Sajjad; Luhur, Muhammad Ramzan; Walasai, Gordhan Das; Alghamdi, Thamer A. H. (Frontiers in Energy Research, 2024)
Recent studies suggest that the world is facing an energy crisis due to the depletion of fossil fuel reserves. To combat this issue, researchers have turned to biodiesel, a renewable bioenergy source made from vegetable oils, microalgae, and animal fats. A recent study analysed engine parts’ particulate matter emissions and carbon deposition during the long-term use of mustard biodiesel and clove oil as antioxidants in a compression ignition engine. Three samples of fuels: DF (diesel fuel), B30 (30% mustard biodiesel and 70% DF), and biodiesel blended fuel with 3000 PPM in a single-cylinder CI engine. The use of 30% biodiesel in diesel fuel (B30) for the endurance test was based on a good mix. The engine was run for 100 h to investigate the particulate matter emissions and carbon deposition. The particulate matter emission data was collected every 25 h, and for carbon deposition, the engine’s fuel injector was turned off after 100 h of engine running. The results showed a reduction in particulate matter emissions of about 9.97%, 13.367%, 7.24%, 14.64%, 5.3%, 12.32%, 1.88%, and 7.99% for PM1, PM2.5, PM7, and PM10 in biodiesel blended fuel and biodiesel blended fuel with clove oil, respectively. The deposition of clove oil added to biodiesel blended fuel in the fuel injector has been reduced compared with the other fuels. Carbon deposition of the fuel injector was analysed through SEM and EDX tests, and the results showed that the carbon content in biodiesel blended fuel was lower than in diesel fuel. The deposition of clove oil added to biodiesel blended fuel in the fuel injector has been reduced compared with biodiesel blended fuel.